2009
DOI: 10.1159/000226588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Lactococcus lactis</i> CLFP 100 and<i> Leuconostoc mesenteroides</i> CLFP 196 on <i>Aeromonas salmonicida </i>Infection in Brown Trout <i>(Salmo trutta)</i>

Abstract: Aeromonas salmonicida is the etiological agent of furunculosis in salmonid fish. This pathogen is important from an epizootic perspective because fish surviving an outbreak can remain lifelong asymptomatic carriers, serving as reservoirs of infection. As a result, the early detection and the control of infection are essential to prevent the spread of new furunculosis outbreaks. We have thus analyzed the effect of probiotic administration on the incidence of A. salmonicida in brown trout (Salmo trutta), that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Lactis in rainbow trout diet and observed increased immune parameters as well as protection against furunculosis (Balcázar et al, 2007 ). The same results observed with brown trout ( Salmo trutta ) challenged with Aeromonas salmonicida (Balcázar et al, 2009 ). Kim et al ( 2013 ) reported that Lc.…”
Section: Probiotics and Bacterial Diseases In Fish (Table 1supporting
confidence: 75%
See 1 more Smart Citation
“…Lactis in rainbow trout diet and observed increased immune parameters as well as protection against furunculosis (Balcázar et al, 2007 ). The same results observed with brown trout ( Salmo trutta ) challenged with Aeromonas salmonicida (Balcázar et al, 2009 ). Kim et al ( 2013 ) reported that Lc.…”
Section: Probiotics and Bacterial Diseases In Fish (Table 1supporting
confidence: 75%
“…The same research group supplemented rainbow trout and brown trout diets with Lc. mesenteroides (10 6 CFU g −1 ) and observed immunomodulation and increased resistance against furunculosis (Balcázar et al, 2007 ) and A. salmonicida infection (Balcázar et al, 2009 ). Dietary application of Lc.…”
Section: Probiotics and Bacterial Diseases In Fish (Table 1mentioning
confidence: 99%
“…Therefore, the current study was aimed at characterization of probiotic and antibacterial properties of L. plantarum VR1 isolated from Kutajarista, against a known cytotoxic and virulent strain, A. veronii . Previously, it has been reported that L. delbrueckii, L. lactis and L. mesenteroides can prevent cellular damage caused by A. salmonicida , a fish pathogen [35,36]. Here we report that VR1 possess strong probiotic properties and abrogated the cytotoxicity of A. veronii MTCC 3249, an isolate from mosquito midgut.…”
Section: Discussionmentioning
confidence: 51%
“…The samples were then processed using the method by Balcázar et al. [4] before storage at −80 °C for further analysis. Also, the same technique used by Balcázar et al.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Also, the same technique used by Balcázar et al. [4] was adopted for gut sample collection, processing, and storage for analysis.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%